2006
DOI: 10.1007/s10495-006-9234-5
|View full text |Cite
|
Sign up to set email alerts
|

α-TEA inhibits survival and enhances death pathways in cisplatin sensitive and resistant human ovarian cancer cells

Abstract: RRR-alpha-tocopherol ether linked acetic acid analog (alpha-TEA), is a potential chemotherapeutic agent for ovarian cancer. Pro-death and pro-life signaling pathways were studied to understand the anti-cancer actions of alpha-TEA on cisplatin-sensitive (A2780S) and -resistant (A2780/cp70R) human ovarian cancer cells. Both cell lines were refractory to Fas; whereas, alpha-TEA sensitized them to Fas signaling. alpha-TEA increased levels of Fas message, protein and membrane-associated Fas. Neutralizing antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…Recently, accumulating evidence indicated that PI3K/Akt pathway plays a crucial role in tumorigenesis and tumor progression by promoting cell proliferation and inhibiting apoptosis. AKT prevents apoptosis by activating anti-apoptotic signals through phosphorylating glycogen synthase kinase 3 (GSK3), Bad and caspase-9 and through activating transcriptional factors, such as forkhead (FOXO-1) and NF-kappa B [10][11][12][13]. In addition, abnormal function of the PI3K/AKT pathway has been reported in many human tumors [9] and this signalling pathway has been suggested to be a potential target for cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, accumulating evidence indicated that PI3K/Akt pathway plays a crucial role in tumorigenesis and tumor progression by promoting cell proliferation and inhibiting apoptosis. AKT prevents apoptosis by activating anti-apoptotic signals through phosphorylating glycogen synthase kinase 3 (GSK3), Bad and caspase-9 and through activating transcriptional factors, such as forkhead (FOXO-1) and NF-kappa B [10][11][12][13]. In addition, abnormal function of the PI3K/AKT pathway has been reported in many human tumors [9] and this signalling pathway has been suggested to be a potential target for cancer chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this study showed that the combination treatment of a-TEA and celecoxib significantly reduced blood-vessel density, as determined by CD-31 staining [12]. An additional rationale for using a-TEA emerges from the fact that a-TEA has been shown to restore Fas/Fas-ligand signaling [13,14]. This signaling, when taken in combination with results from studies showing that UV-damaged keratinocytes are eliminated by the Fas/Fas-ligand interaction -but also that this pathway becomes dysregulated during UV skin carcinogenesis [15,16] -suggests a potential relevant target for a-TEA in UV-induced skin cancer.…”
Section: Introductionmentioning
confidence: 80%
“…α-TEA has increased apoptotic activity compared to αTS in several cancer cell lines and decreases tumor burden and metastasis in mouse cancer models (116). α-TEA modulates cellular signaling by activating JNK and its substrate c-Jun, and mediates a conformational change in Bax, triggering cleavage of Bid and caspases-8, -9, and -3 (265). α-TEA also decreases phosphorylation of PKB and ERK1/2 and lowers the cellular FLICE-like inhibitory protein and survivin protein levels (265).…”
Section: Synthetic Vitamin E Analogues and Signal Transductionmentioning
confidence: 99%
“…α-TEA modulates cellular signaling by activating JNK and its substrate c-Jun, and mediates a conformational change in Bax, triggering cleavage of Bid and caspases-8, -9, and -3 (265). α-TEA also decreases phosphorylation of PKB and ERK1/2 and lowers the cellular FLICE-like inhibitory protein and survivin protein levels (265). In breast cancer cell lines, α-TEA suppressed constitutively active basal levels of pPKB, pERK, pmTOR, and their downstream targets as well as induced apoptosis involving insulin receptor substrate-1/PI3K and JNK (234).…”
Section: Synthetic Vitamin E Analogues and Signal Transductionmentioning
confidence: 99%